2002
DOI: 10.1034/j.1600-0722.2002.21326.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐crystallite nanoretention of self‐etching adhesives at enamel imaged by transmission electron microscopy

Abstract: The purpose of this in vitro study was to analyse the mode of action of self-etching adhesive systems when applied for resin-to-enamel bonding. Transmission electron microscopy was used to investigate the enamel-resin interface after application of non-rinsing self-etching adhesive systems based on phosphoric acid estered methacrylates (Clearfil Liner Bond 2, Clearfil SE Bond, Etch & Prime 3.0 and Resulcin AquaPrime) compared with conventional phosphoric acid etching and bonding (Heliobond). Non-decalcified ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
109
1
16

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(131 citation statements)
references
References 19 publications
3
109
1
16
Order By: Relevance
“…[22][23][24][25][26] The high bond strength with the use of self-etch primers has been attributed to nanoretentive interlocking between the enamel crystallites and the resin, potential resin-to-enamel bonding, and chemical bonding. 11,27 After the third debonding, the bond strength was not different among the three adhesive systems. Transbond demonstrated no change in bond strength from rebonding, but the other two adhesive systems demonstrated an increase in bond strength.…”
Section: Discussionmentioning
confidence: 92%
“…[22][23][24][25][26] The high bond strength with the use of self-etch primers has been attributed to nanoretentive interlocking between the enamel crystallites and the resin, potential resin-to-enamel bonding, and chemical bonding. 11,27 After the third debonding, the bond strength was not different among the three adhesive systems. Transbond demonstrated no change in bond strength from rebonding, but the other two adhesive systems demonstrated an increase in bond strength.…”
Section: Discussionmentioning
confidence: 92%
“…However, in view of the high permeability of enamel to hydrogen peroxide, it is likely that the entire thickness of enamel might be modified by such prolonged treatments, regardless of the surface used 13 . The mechanism of bonding to enamel with self-etching primers has been reported to be more superficial than that of total-etch adhesives and based on inter-and intra-crystallite hybridization of 0.6 to 0.7 µm into enamel 7 . Since deeper etching pattern and long resin tags in phosphoric acid-etched specimens can be obtained with Single Bond, little effect was produced on the bond strength of the total-etch adhesive.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, results showed that the bond strength of the total-etch adhesive was always higher than that of the self-etching primer on enamel surfaces. The bleaching treatment could promote an additional effect on the surface, leading to an unpredictable bonding to enamel with the self-etching adhesive 7 . Some studies have evaluated the bond strength of self-etching adhesive systems to enamel and the controversial results have shown that bonding to enamel should be improved 15,22 or that it is similar to total-etch adhesives 10,19 .…”
Section: Discussionmentioning
confidence: 99%
“…24 Thus, the clinical use of self-etching adhesives to enamel for resin bonding still has to be confirmed by long-term clinical studies. 8 The purpose of this in vitro study was to evaluate the effect of phosphoric acid etching of enamel margins on the microleakage of a self-etching adhesive (Clearfil SE Bond: CSEB) and a simplified all-in-one adhesive system (iBond: IB) in comparison with that of a total-etch adhesive system (Scotchbond Multi-Purpose: SBMP).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7] The bond strength of resin composites to acid-etched enamel is typically in the range of 20-25 Mpa and provides routinely successful retention of resin composites for a variety of clinical applications. 8 Enamel pre-treatment could be simplified by the use of self-etching and all-in-one adhesive systems. These adhesive systems rely on simultaneous etching of dentin and enamel with weaker acids than the traditional 30%-40% phosphoric acid etchants.…”
Section: Introductionmentioning
confidence: 99%